Draft Annual Plan 1981-82 Administration of Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1981)
The Union Territory of Dadra and Nagar Haveli is situated near the Western Coast of India adjacent to the Bulsar District and has an area of 491 Sq. Km. This Territory was in a different stream than the rest of the country for about two centuries. In 1947 when rest of the country breathed an air of freedom, this part of the country continued to be under the yoke of foreign rule and it was only in 1954 that the people of the Territory threw away the regime of Portuguese rulers and achieved independence.
Administration of Union Territory of Dadra and Nagar-Haveli